Effects of Essential Fatty Acids Containing Natural and Commercial Diets on Larvae Rearing of the Green Mud Crab Scylla Paramamosain (Estampador 1949) (Journal of Scientific Research, 2017)
Effect of essential fatty acids (EFA) on growth and survival of the green mud crab (Scylla paramamosain) larvae was assessed by feeding with natural to commercial diets. The feeding schemes were: larvae reared with Artemia (T1); larvae initially fed with rotifers (up to Z2) and ended (Z3 to megalopa) with Artemia (T2); and larvae fed with rotifers up to Z2 and ended (Z3 to megalopa) with commercial diet (T3). The commercial diet had significantly (p